Trump tariffs and roundabout trade - Tadashi Ito (KDI Journal of Economic Policy, 2024)
Although there are many news articles of tariff dodging via the re-routing of made-in-China goods through third countries, relabeling these goods as made in Mexico or made in Vietnam, there have been no scientific studies on this issue. This paper provides statistical evidence regarding whether such practices are taking place. Using monthly trade statistics at the most disaggregated level and analyzing data up to 2019, the year before the COVID-19 shock, little evidence of roundabout trade is found. With an extended dataset up to 2023, overall there is little sign of roundabout trade, although some slight signs of roundabout trade are found for Mexico and Vietnam.
Keywords: F14; 330; Trump Tariffs; Roundabout Trade